Biphasic Supramolecular Self‐Assembly of Ferric Ions and Tannic Acid across Interfaces for Nanofilm Formation. Issue 28 (19th May 2017) - Kim, Beom Jin; Han, Sol; Lee, Kyung‐Bok; Choi, Insung S.
Abstract : Cell nanoencapsulation provides a chemical tool for the isolation and protection of living cells from harmful, and often lethal, external environments. Although several strategies are available to form nanometric films, most methods heavily rely on time‐consuming multistep processes and are not biocompatible. Here, the interfacial supramolecular self‐assembly and film formation of ferric ions (Fe III ) and tannic acid (TA) in biphasic systems is reported, where Fe III and TA come into contact each other and self‐assemble across the interface of two immiscible phases. The interfacial nanofilm formation developed is simple, fast, and cytocompatible. Its versatility is demonstrated with various biphasic systems: hollow microcapsules, encasing microbial or mammalian cells, that are generated at the water–oil interface in a microfluidic device; a cytoprotective Fe III –TA shell that forms on the surface of the alginate microbead, which then entraps probiotic Lactobacillus acidophilus ; and a pericellular Fe III –TA shell that forms on individual Saccharomyces cerevisiae . This biphasic interfacial reaction system provides a simple but versatile structural motif in materials science, as well as advancing chemical manipulability of living cells. Abstract : The biphasic interfacial supramolecular self‐assembly of ferric ions (Fe III ) and tannic acid in a heterogeneous system provides a powerful method for the formation of uniform and stable nanofilms in one step. The versatility of the synthetic strategy is demonstrated under various experimental settings (water–oil, hydrogel–water, and cell–water biphasic systems).